Patterns of fish consumption by hunter-fisher-gatherer people from the Atlantic coast of Tierra del Fuego during the Holocene: Human-environmental interactions. (April 2023) - Bas, Maria; Salemme, Mónica; Santiago, Fernando; Briz i Godino, Ivan; Álvarez, Myrian; Cardona, Luis
Abstract: This paper aims to assess changes in the patterns of marine fish consumption by hunter-fisher-gatherer populations in the context of environmental change. To accomplish this objective, we used two methodological approaches: first, stable isotope analysis in ancient and modern shells of limpets and mussels to explore changes in the isotopic baseline and also in fish skeletal remains recovered from different archaeological sites dated to the Middle and Late Holocene of Tierra del Fuego (Argentina); second, a zooarchaeological quantitative analysis of the fish remains from different archaeological sites in the same area and period. Results confirmed that marine primary productivity in the Atlantic coast of Tierra del Fuego decreased throughout the second half of the Holocene, while the contribution of phytoplankton to the carbon pool fueling the coastal food web decreased simultaneously. The quantitative zooarchaeological analysis and the stable isotope analyses in fish remains suggest that in the Atlantic coast there was a variation in the consumption of fish species from offshore to near shore fish species throughout time, mostly because of the declining occurrence of Argentine hake ( Merluccius hubbsi ). This could result from changes in the distribution of the latter and the probability of mass stranding. Highlights: Marine primary productivity in the Atlantic coast of Tierra del Fuego decreased throughout the Late Holocene. The diversity of marine resources used by human populations inhabiting this region decreased from the Middle to Late Holocene. Declining marine primary productivity and sea surface temperature during the Late Holocene likely reduced the offshore fish species availability.